Two-dimentional diffractive optical structure based on patterned photoalignment of polymerizable liquid crystal - Kabanova, Olga S.; Rushnova, Iryna I.; Melnikova, Elena A.; Tolstik, Alexei L.; Muravsky, Alexander A.; Murauski, Anatoli A.; Heintzmann, Rainer (Journal of the Belarusian State University. Physics, 2019)
This paper is devoted to the investigation of the diffraction characteristics of a multilayer optical structure, represented by a two-dimensional phase lattice formed in thin-film layers of nematic polymerizable liquid crystal (PLC). In order to generate periodically ordered liquid-crystal (LC) domains with dimensions of 5–10 µm, which form an anisotropic LC grating, the layer-by-layer patterned photoalignment technology of the water-soluble azo dye AbA-2522 was used. The possibilities of spatial-polarization control of light beams by means of developed one- and two-dimensional diffractive LC structures have been studied experimentally. Our results are promising from the point of view of development and creation of LC-devices for solving current problems of polarization photonics.